Theories and Applications of School Motivation: Exploring the Reciprocal Relationship with Academic Achievement in Latin America - Vela, Dennis Renato Manzano; Mancheno, Ana Carola Flores; Castelo, Edison Marcelo Salas; Chávez, Marco Vinicio Parra (Journal of Ecohumanism, 2024)
The present study provides a comprehensive systematic review of the impact of motivation in educational settings, emphasizing its crucial role in fostering effective learning. Key theories of motivation, such as self-determination theory, the ARCS (Attention, Relevance, Confidence, and Satisfaction) model, social cognitive theory, and expectancy theory, are discussed in detail. Through this review, the reciprocal dynamics between motivation and academic performance are highlighted, suggesting that these interactions are significant but complex. The urgency for further studies that can establish clear and robust causal relationships between these factors is underscored, which could revolutionize current pedagogical strategies. In addition, potential educational interventions based on these findings are proposed and future lines of research are pointed out that could further explore how motivation influences and can be manipulated to improve academic outcomes.